Eumelanin Graphene-Like Integration: The Impact on Physical Properties and Electrical Conductivity - Di Capua, Roberto; Gargiulo, Valentina; Alfè, Michela; De Luca, Gabriella Maria; Skála, Tomáš; Mali, Gregor; Pezzella, Alessandro (Frontiers in Chemistry, 2019)
The recent development of eumelanin pigment-based blends integrating "classical" organic conducting materials is expanding the scope of eumelanin in bioelectronics. Beyond the achievement of high conductivity level, another major goal lays in the knowledge and feasible control of structure/properties relationship. We systematically investigated different hybrid materials prepared by in situ polymerization of the eumelanin precursor 5,6-dihydroxyindole (DHI) in presence of various amounts of graphene-like layers. Spectroscopic studies performed by solid state nuclear magnetic resonance, x-ray photoemission and absorption spectroscopies gave a strong indication of the direct impact that the integration of graphene-like layers into the nascent polymerized DHI-based eumelanin has on the structural organization of the pigment itself, while infrared and photoemission spectroscopies indicated the occurrence of negligible changes as concerns the chemical units. A tighter packing of the constituent units could represent a strong factor responsible for the observed improved electrical conductivity of the hybrid materials, and could be possible exploited as a tool for electrical conductivity tuning.